2013
DOI: 10.2139/ssrn.3199036
|View full text |Cite
|
Sign up to set email alerts
|

How Ontologies are Made: Studying the Hidden Social Dynamics Behind Collaborative Ontology Engineering Projects

Abstract: Traditionally, evaluation methods in the field of semantic technologies have focused on the end result of ontology engineering efforts, mainly, on evaluating ontologies and their corresponding qualities and characteristics. This focus has led to the development of a whole arsenal of ontologyevaluation techniques that investigate the quality of ontologies as a product. In this paper, we aim to shed light on the process of ontology engineering construction by introducing and applying a set of measures to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Strohmaier et al [23] investigated the hidden social dynamics that take place in collaborative ontology-engineering projects from the biomedical domain and provides new metrics to quantify various aspects of the collaborative engineering processes. Wang et al [24] have used association-rule mining to analyze user editing patterns in collaborative ontologyengineering projects.…”
Section: Collaborative Ontology Engineeringmentioning
confidence: 99%
“…Strohmaier et al [23] investigated the hidden social dynamics that take place in collaborative ontology-engineering projects from the biomedical domain and provides new metrics to quantify various aspects of the collaborative engineering processes. Wang et al [24] have used association-rule mining to analyze user editing patterns in collaborative ontologyengineering projects.…”
Section: Collaborative Ontology Engineeringmentioning
confidence: 99%
“…We and other investigators have used change data from ontologies to measure the level of community activities in biomedical ontologies [14], to migrate data from an old version of an ontology to a new one [12], and to analyze user roles in the process of collaboration [6,7,23,26]. For example, we have demonstrated that we can use the change data to assess the level of stabilization in ontology content [26], to find implicit user roles [7], and to describe the collaboration qualitatively [23]. For example, we found that changes to ICD-11 tend to propagate along the class hierarchy: A user who alters a property value for a class is significantly more likely to make a change to a property value for a subclass of that class than to make an edit anywhere else in the ontology [19].…”
Section: Collaborative Ontology Development and Related Workmentioning
confidence: 99%
“…Protégé at the beginning was viewed merely as a means to an end. More recent grants, however, have supported our original research to study collaborative ontology development (Tudorache et al, 2011; Strohmaier et al, 2013), methods for ontology alignment (Noy and Musen, 2003; Ghazvinian et al, 2009), ontology evaluation through crowdsourcing (Mortensen et al, 2014), ontology visualization (Storey et al, 2001), and methods for the very early stages of ontology conceptualization (Zhang et al, 2015). These academic pursuits are what make our laboratory an exciting place for students and post-docs, and they are what keep the research funding flowing.…”
Section: What Is Our Core Mission Anyway?mentioning
confidence: 99%